Cryo-electron microscopy reveals two distinct type IV pili assembled by the same bacterium - Alexander Neuhaus (Nature Portfolio, 2020)
Type IV pili are flexible filaments on the surface of bacteria, consisting of a helical assembly of pilin proteins. Here, Neuhaus et al. show that the bacterium Thermus thermophilus produces two forms of type IV pilus, differing in structure, protein composition, and function.